Exploring factors influencing phonological errors of Indonesian EFL students - Marelita, Dema Finda; Iftanti, Erna (Journal of English Language Teaching and Learning (JETLE), 2024)
For non-native English speakers, phonological errors posed a serious problem, especially for those from Indonesia, where the local language's phonological structure is very different from English's. The goal of the study was to determine the elements that lead to phonological errors in Indonesian EFL students' sound production. Using a descriptive qualitative methodology, the study examined the factors that lead to growing errors in English phonology by analyzing several article and process them into new idea. The researchers looked at a number of variables, such as the learners' exposure to English and linguistic background, that affect these errors. The study also looked at how these elements work together to affect how Indonesian learners produce sounds. This study found several factors emerging phonological errors of Indonesian EFL student, they are phonetic system gap, social condition, and lack of phonological awareness. The study's emphasized how crucial it is to teach English pronunciation while taking the learners' native tongue and cultural background. EFL teachers should be aware of the variations in the phonological systems of English and Indonesian and implement teaching strategies that take these differences. Furthermore, the sociolinguistic and socioeconomic circumstances of the students had an impact on the phonological errors,